use the distributive prperty to rewrite the expression without parentheses.

1. (-2a)(a+7)
2. (-3x)(-x^2+2)
3. (2x + 11)(5x)
4. (-2-3y)(-7y^2
5. (t-4)(-2)
6. (x)(x-5)

Again, 1. -2a^2 - 14a

Please only post your questions once. Repeating posts will not get a quicker response. In addition, it wastes our time looking over reposts that have already been answered in another post. Thank you.

To use the distributive property and rewrite expressions without parentheses, you need to distribute each term in the parentheses to every term outside of it. Here's how you can rewrite each expression without parentheses:

1. (-2a)(a + 7) = -2a * a + (-2a * 7) = -2a^2 - 14a

2. (-3x)(-x^2 + 2) = (-3x * -x^2) + (-3x * 2) = 3x^3 - 6x

3. (2x + 11)(5x) = (2x * 5x) + (11 * 5x) = 10x^2 + 55x

4. (-2 - 3y)(-7y^2) = (-2 * -7y^2) + (-3y * -7y^2) = 14y^2 + 21y^3

5. (t - 4)(-2) = (t * -2) + (-4 * -2) = -2t + 8

6. (x)(x - 5) = x^2 - 5x

By applying the distributive property, each expression is rewritten without parentheses.